Decreased clot burden is associated with factor XIII Val34Leu polymorphism and better functional outcomes in acute ischemic stroke patients treated with intravenous thrombolysis. - István Szegedi (Public Library of Science (PLoS), 2021)
Background Intravenous thrombolysis using recombinant tissue plasminogen activator remains the mainstay treatment of acute ischemic stroke (AIS), although endovascular treatment is becoming standard of care in case of large vessel occlusions (LVO). To quantify the thrombus burden in LVO, a semiquantitative CT angiography (CTA) grading system, the clot burden score (CBS) can be used. Here we aimed to study the association between CBS and various hemostasis parameters, and to evaluate which parameters are major determinants of thrombolysis outcome. Methods In this single-centered prospective observational case-control study, 200 anterior circulation AIS patients receiving intravenous thrombolysis treatment without thrombectomy were enrolled: 100 AIS patients with LVO (CBS 0-9) and 100 age- and sex-matched AIS patients without LVO (CBS 10). Fibrinogen, α2-plasmin inhibitor, plasminogen, factor XIII and D-dimer were assessed from blood samples taken before and 24 h after thrombolysis, and FXIII-A Val34Leu was genotyped. CBS was calculated using admission CTA. Short-term outcomes were defined based on the change in NIHSS by day 7, long-term outcomes were assessed according to the modified Rankin scale at 3 months post-event. Results Poor outcomes were significantly more frequent in the CBS 0-9 group. Plasminogen activity on admission was significantly higher in the CBS 0-9 group. In a univariate analysis, significant protective effect of the Leu34 allele against developing larger clots (CBS 0-9) could be demonstrated (OR:0.519; 95%CI:0.298-0.922, p = 0.0227). Multivariate regression analysis revealed that CBS is an independent predictor of short- and long-term functional outcomes, while such effect of the studied hemostasis parameters could not be demonstrated. Conclusions CBS was found to be a significant independent predictor of thrombolysis outcomes. FXIII-A Leu34 carrier status was associated with smaller thrombus burden, which is consistent with the in vitro described whole blood clot mass reducing effects of the allele, but the polymorphism had no effect on thrombolysis outcomes.